Early detection of neonatal hypoxic–ischemic white matter injury: an MR diffusion tensor imaging study. Issue 13 (6th September 2017) - Seo, Youngseob; Kim, Geun-Tae; Choi, Jin Wook
Abstract : The purpose of this study was to compare diffusion tensor metrics in normal age-matched neonates with survivors of hypoxic–ischemic encephalopathy (HIE) and extracorporeal membrane oxygenation (ECMO). Thirty-five normal, 27 HIE, and 13 ECMO infants underwent MRI at 3 T. Neurodevelopmental assessments were performed. Fractional anisotropy (FA), axial diffusivity (AD), and radial diffusivity (RD) of the inferior fronto-occipital fasciculus, inferior longitudinal fasciculus, anterior commissure, genu corpus callosum and splenium of the corpus callosum, anterior and posterior limb of the internal capsule, superior longitudinal fasciculus, and the centrum semiovale were analyzed with tract-based spatial statistics modified for use in neonates. Linear regression analysis was performed, and 95% confidence intervals were created for age effects on the tensor metrics with the control patients. Two-sample t -test was done to determine whether there was a difference in the tensor metrics between the normal and patient cohort. There was a statistically significant age effect on the FA and RD in the selected regions of the brain ( F <0.05) and a group difference in the FA and RD between the normal and the HIE group ( P <0.05). The group difference in the FA and RD between the normal and ECMO groups was seen in the anterior commissure, genu corpus callosum, right inferior longitudinal fasciculus, fronto-occipital fasciculus, centrum semiovale, and superior longitudinal fasciculus ( P <0.05). Patients who were outside the 95% confidence intervals of the FA, AD, and RD overlapped with those with abnormalities clinically and on the conventional MRI. In conclusion, diffusion tensor imaging can play a significant role in detecting infants with early indications of hypoxic–ischemic brain injury.